Excluding parental grief: A critical discourse analysis of bereavement accommodation in Canadian labour standards. - Macdonald, Mary Ellen; Kennedy, Kimberly; Moll, Sandra; Pineda, Carolina; Mitchell, Lisa M.; Stephenson, Peter H.; Cadell, Susan (Work, 2015)
BACKGROUND: Grief following child loss is profoundly destabilizing with serious long-term repercussions for bereaved parents. Employed parents may need time away from work to deal with this loss.OBJECTIVE: The purpose of this study was to reflect upon the ways labour policies and practices respond to parental bereavement.METHODS: Critical discourse analysis was used to examine labour policies and practices related to employment leave for bereaved parents in Canada. Results were compared to international labour standards.RESULTS: Universally, employment policies provide only for the practical issues of bereavement. Commonly, leave is three days, unpaid, and meant to enable ceremonial obligations. Policies do not acknowledge the long-term suffering caused by grief or the variable intensity of different kinds of loss. Managerial, moral, normative and neoliberal values embedded in these policies efface the intensely personal experience of grief, thereby leaving employees at risk for serious health and workplace safety issues.CONCLUSIONS: Bereavement leave currently understands grief as a generic, time-limited state with instrumental tasks and ceremonial obligations. In contrast, research characterizes responses to child loss as intense, highly personal experiences for which healing and recovery can take years. This disconnect is especially problematic when viewed through the lens of employee wellbeing, reintegration and workplace productivity.